DO COMPANY FUNDAMENTALS AFFECT GOING CONCERN AUDIT OPINION? - Amrie Firmansyah; Priscilla Oliviane Ngesthi; Ricy Dwi Agustin; Estralita Trisnawati (Kesatuan Press, 2023)
Essential information from the company indicates potential and existing investors in investing their funds. Through these indicators, shareholders can analyze the company's sustainability in the future so that this information can be used in investments. However, companies are only sometimes at their best. Thus, this study determines the effect of profitability, operating cash flow, and liquidity on going concern audit opinion. This study employs data from transportation companies listed on the Indonesia Stock Exchange/IDX from 2019 to 2021. The sample selection technique employed in this study is purposive sampling, with 47 observations. The test employed in this study is the logistic regression. This study concludes that profitability and liquidity are not associated with going concern audit opinion, while operating cash flow is negatively associated with going concern audit opinion. This study suggests that operating cash flow is essential information that can be an early indication of risk mitigation that must be carried out for the company’s going concern.